Identification of Science Process Skills Making Tables and Graphs for High School Students on Biology Materials - Budhi Akbar; Alfi Delvira; Maesaroh Maesaroh (STAI Hubbulwathan Duri, 2023)
Science process skills are a crucial instrument for learners to acquire competence through engaging in various learning activities. One facet of science process skills involves the utilisation of communication abilities, which may be effectively demonstrated through the creation of tables and graphs. Scientific communication encompasses both vocal and written forms of expression. Tables and graphs are commonly employed as effective instruments for delivering scientific knowledge or research findings communicatively. The objective of this study is to assess the proficiency of students in employing science process skills, specifically in the creation of tables and graphs, as well as to examine the potential correlation between these two skills. The employed research methodology is the descriptive correlational approach. Class XI science students from senior high school in Bogor Regency in the 2021/2022 school year were included in this study. There were a total of 240 students across 7 classes. Class XI Science 1 and XI Science 5 were used as samples in this research, with a total of 72 students. Cluster random sampling was used for the study's data collection. The study's findings indicate that students' Science Process Skills, specifically their ability to create tables and graphs, fall within the sufficient group. 2) The correlation between science process abilities and proficiency in creating tables and graphs falls within the poor category. 3) The proportion of the ability to create tables that accounts for the capacity to create graphs is 11%.